Morphological and Molecular Diversity of Five Superior Napier Grass Cultivars in Indonesia - Nasution, M. D. M.; Umami, N.; Kurniawati, A.; Rahman, M. M. (Faculty of Animal Science, IPB University, 2025)
This study aimed to evaluate the morphological and genetic diversity among five cultivars of Napier grass (Pennisetum purpureum) grown in Indonesia: ‘Gama Umami’, ‘Pakchong’, ‘Odot’, ‘Purple’, and ‘Local’. A total of 20 plants per cultivar were planted in a completely randomized design with morphological parameters, nutrient content, biomass production, and molecular analysis assessed at a cutting age of 90 days. The morphological analysis revealed significant differences (p<0.05) in plant height, leaf length, and the number of tillers across the cultivars. Qualitative analysis revealed differences in leaf color and growth habits. ‘Gama Umami’ cultivar showed the highest biomass yield, with significantly (p<0.05) higher crude protein and dry matter content than the other cultivars. Random amplified polymorphic DNA (RAPD) analysis using nine primers on the five Napier grass cultivars demonstrated diverse band patterns, resulting in a percentage of polymorphic bands (PBP) ranging from 60% to 100%. The dendrogram derived from the RAPD data clustered the cultivars into two main groups, with ‘Gama Umami’ and ‘Local’ showing a high similarity coefficient of 0.73, while ‘Purple’ and ‘Pakchong’ formed a distinct sub-cluster with a similarity coefficient of 0.66, and ‘Odot’ exhibited a similarity coefficient of 0.58 with the ‘Purple’ and ‘Pakchong’ sub-cluster. This study revealed significant genetic and morphological diversity among five Napier grass cultivars, with 'Gama Umami' demonstrating superior morphological traits, nutrient content, and biomass production. These findings highlight the potential of integrating molecular and morphological analyses to support breeding programs for improving forage quality and productivity.